Bringing social values to wildlife conservation decisions. Issue 6 (3rd June 2021) - Manfredo, Michael J; Berl, Richard EW; Teel, Tara L; Bruskotter, Jeremy T
Abstract : Humans regularly exert a powerful influence on the survival and persistence of species, yet social‐science information is used only sporadically in conservation decisions. Using data obtained from a survey of 46, 894 US residents, we developed and applied a spatially explicit "sociocultural index" to inform decision making through an understanding of public values toward wildlife. The classification is defined by opposing values of mutualism and domination, which have been previously shown to be highly predictive of attitudes on a wide range of policy issues. We developed state and county maps that can be used to represent public interests in policy decisions and inform management actions that target human behavior, such as education. To illustrate, we present findings indicating a supportive social context for gray wolf ( Canis lupus ) reintroduction in Colorado, an issue voted on and passed through a November 2020 citizen ballot initiative. Although the results are particularly relevant for the US, the technique is broadly applicable and its expansion is encouraged to better account for human factors in conservation decisions globally.